Implementation Of Rapid Entire Body Assessment Method and Design of Assistant Tools In The Carton Box Companies - Lucky Setiawan; Dina Rosdiana; Dedy Khaerudin; Ganjar Sidik Gandara; Najmuddin Najmuddin (Industrial Engineering, Faculty of Engineering, Universitas Sebelas Maret, 2025)
Work-related musculoskeletal disorders (WMSDs) are a major problem for employers and employees in the workplace. These disorders can usually be found in several processes that are still carried out manually. Manual work is still an important component in various industrial and service sectors in the modern era. Although technological advances have automated many processes, a large number of workers are still involved in tasks that require physical strength, repetitive movements, and unnatural postures. One of the cardboard box companies in the Banten area has manual work that is at risk of WMSD. One of the jobs analyzed was in the packaging division in the binding process. From the results of the REBA sheet analysis, the initial condition of the job had a value of 9 which was classified as a high-risk job. By making improvements by designing a binding aid to be used as an aid, the work posture assessment can be reduced to 3, which means that the job is classified as low risk